Iron doped magnesium chromite spinel and LSM coating to diminish chromium poisoning in the SOFC cathode environment - Unsal, Huseyin; Majee, Rahul; Veronese, Andrea; Ozkan, Selda; Connor, Paul; Naden, Aaron; Boynuegri, Tugba A.; Savaniu, Cristian; Irvine, John T. S. (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Solid oxide fuel cells (SOFCs) suffer from degradation issues primarily arising from their high operating temperatures. Among the most critical degradation mechanisms is cathode poisoning by volatile chromium species from Fe-Cr-based metallic interconnects. A widely adopted strategy to mitigate this problem involves applying protective surface coatings to the interconnects. In this study, protective layers were deposited on AISI 430 stainless steel using the screen-printing method. A bilayer coating comprising a chromium-rich spinel (MgFe0.1Cr1.9O4) and a perovskite (La0.65Sr0.35)(0.95)MnO3 (LSM) was applied to enhance oxidation resistance and minimise the increase in electrical resistance. Three types of substrates, bare, single-layer LSM-coated, and bilayer (spinel-perovskite) coated, were subjected to 1000-h oxidation at 800 degrees C in static air, simulating SOFC cathode operating conditions without electrical load. The bilayer-coated steel exhibited excellent long-term durability, with no detectable chromium migration from the steel or spinel layer to the LSM surface. The chromite spinel layer significantly improved LSM adhesion, prevented cracking and buckling, and maintained a stable oxide layer thickness (similar to 3 mu m) at the coating-substrate interface. The area-specific resistance (ASR) of the bilayer-coated steel remained low, measured at 0.056 Omega cm(2) after 1000 h, outperforming both the uncoated and LSM monolayer coated samples.
Keywords: OXIDE FUEL-CELLS; FERRITIC STAINLESS-STEEL; METALLIC INTERCONNECTS; OXIDATION BEHAVIOR; ELECTRODES; ALLOY; COBALT; Chemistry; Electrochemistry; Energy & Fuels